PERAN GURU PAI DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SMAN 1 CERME GRESIK - Maftuh Maftuh; Zahrotul Widdad Wusannah (JP : JURNAL PENDIDIKAN, 2021)
Abstract: Islamic religious education is very important for students to establish good relationships with their creators and with other creatures along with growing spiritual attitudes. Islamic religious education aims to shape the religious character of each student in accordance with the goals of education in Indonesia. SMAN 1 Cerme is a public school whose students adhere to various religions so that religious character in the form of tolerance with other religions must be instilled in each student.This study uses a descriptive qualitative approach, with data analysis using data reduction, data presentation and conclusion drawing. The data collection techniques using observation, interviews and documentation. For the validity of the data using tringulation technique.The results showed: PAI teachers play an active role in shaping the religious character of students. In forming a religious character in the form of tolerance to friends of different religions, PAI teachers always give advice to respect and respect each other even though they are of different religions. Supporting factors in shaping religious character are the school's vision and mission and adequate infrastructure, as well as a sense of humility 'of the students with the teachers or employees at the school. The inhibiting factor is the lack of parental participation in existing programs in schools.Keywords: Religious Character, Character Educaion, Islamic Education